(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Like race and ethnicity, gender is a social construct. The innate biological differences between females and males are interpreted by society to create a set of social expectations that determine differential access to rights, resources, and power in society. In a gender neutral society, it is expected that females who constitute almost half of the population must benefit along with males from any improvement that occurs. Employment is one of the ways to empower females in the society. But in Indian economy, more precisely in Haryana, work participation rate of males dominate over females in activities recognized to be economically productive. Various census reports have recorded relatively low level of labour force participation of females, which is an indication of favour to males resulting in an unequal sharing of power and a gender inequality that exists in Haryana. It also explores some factors determining the level of female work participation rate. Gender equality is more than a goal in itself. It is a precondition for meeting the challenges of reducing poverty, promoting sustainable development and building good governance Kofi Annan Inequality between men and women is one of the most crucial disparities in many societies, and this is particularly so in India. On one level, gender disparity can be narrowly defined as the purely descriptive observation of different outcomes between males and females. The variables chosen for examination include those, which have a bearing on gender and equity issues. We found that in Haryana, there is decrease in gender disparities during last decade but the rate of this is very slow.